Objetifi cation of woman: gender implications in the imminence of bariatric surgery - Franco, Suelen [UNESP]; Vieira, Carla Maria [UNESP]; de Oliveira, Maria Rita Marques [UNESP] (FapUNIFESP (SciELO), 2022)
Bariatric surgery, performed predominantly in women (80% in Brazil and 77% in global average), represents, in addition to the prevention of risks to health problems, a promise of subjective well-being. In this work, we analyzed, from the perspective of feminist and psychodynamic theories, associated with the health literature, narratives, and non-verbal expressions of a group of women on the verge of such surgery. The results obtained showed that that group of women sought surgery as a device to achieve the thinness as a socially idealized female standard. The fat body was recognized as a non-human condition and the surgery symbolized the release of that condition and the rescue of sexuality. It was concluded, therefore, that gender issues must be recognized to support health teams in order to mitigate unrealistic expectations and improve the outcome of the treatment of severe obesity.
Objetivación de la mujer: implicaciones de género en la inminencia de la cirugía bariátrica
Objetifi cação da mulher: implicações de gênero na iminência da cirurgia bariátrica
Keywords: Bariatric surgery; Gender; Obesity; Qualitative research; Women